Media “Teka-Teki Silang” Implementasi Metode Design Thinking Dalam Pembelajaran Bahasa Indonesia Kelas VIII SMP Negeri 8 Palembang - R, Rohani; Agustina, Juaidah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Learning media is important to attract attention and create active interaction of students in the learning process so that learning activities will be effective and efficient. The selection of learning media before being applied must be selected according to the needs of students so that the learning process will be easier to achieve the desired goals. In this study, the selection of learning media to be used was selected according to the Design Thinking method. Design thinking is a problem-solving design innovation. The Design Thinking method goes through five stages: empathize, define, ideation, prototype and test. With the initial activity of finding the source of the problem, creating a model design, solving the problem with a prototype and at the end of the activity finding a new innovation that is appropriate as a form of solution to the existing problem by implementing the "Crossword" media to help students be interested and motivated in learning Indonesian in the material of the observation report results of class VIII in groups. It is expected that with the use of this media the learning process can run effectively and interactively in accordance with the objectives of the design that has been prepared.